Effects of the use of semaglutide as a pharmacological option for weight loss in adults with BMI > 25 Kg/m²: a scoping review (Research, Society and Development, 2023)
Introduction: Obesity is a chronic disease resulting from the functional metabolic impairment of the body, whose main consequence is secondary cardiovascular diseases, presenting, therefore, overweight as a risk factor in adults. Therefore, it became essential to search for a pharmacological approach to help change eating habits and routine physical activities, in order to minimize the chances of development and recurrence of the disease. Objective: to evaluate the drug potential of semaglutide as an adjuvant therapy for weight loss in adults who demonstrate body mass index values ​​above 25. Methodology: this is a Scope Review, carried out from September to October 2022, through a survey in the MEDLINE database using the Mesh Terms used in the search using the PubMed platform. For the review, 20 articles were selected, which met the eligibility criteria. Results: the main findings evidenced the benefits of the drug for sustained weight loss in obese patients, reduction of cardiometabolic risk and improvement of glycemic control. In addition to natriuretic and diuretic effects, which reduce blood pressure and improve inflammatory processes. Conclusion: although there is no definitive consensus in the scientific community on the possible effects associated with the use of semaglutide, the literature converges in the same direction regarding the consolidation of semaglutide as a promising drug in the weight loss process of overweight and obese adults.